Pendampingan Kesehatan Mental Keluarga dalam Upaya Pencegahan Depresi dan Bunuh Diri Pada Ibu Muda di Wilayah Kecamatan Papar: - Hanur, Binti Su'aidah; Syah, Muhamad Arifudin; Dzulfiqar, Febri Ardhi Ahmad (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The marriage rate for the 15-19-year-old group in urban areas is lower than in the countryside. This phenomenon has a lot of negative effects especially on teenage girls. The problem arising from early marriage among them is the contribution to the high rate of early divorce and domestic violence. The aim of this dedication to society is to build synergy of the role of stakeholders or related bureaucracy to reduce the depression and suicide rates. The method used in this collaboration is participatory action research (PAR). The impact of the change that can be observed is the presence of a good emotional development demonstrated by the participants in which the participants consciously begin to adapt to their own personal lives. Participants began to be able to accept the shortcomings of their respective partners and focused on parenting as their next  generation.